Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/admi.202202429
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Encapsulation and Doping of Monolayer MoS2 by In Situ Probing of Excitonic Properties During Atomic Layer Deposition

Abstract: suppressed, they may replace or augment silicon (Si) to overcome scaling and performance limitations of current semiconductor technologies. [5] However, few-and single-layer 2D materials are supremely sensitive to their dielectric environments, which must be controlled on the atomic level in a scalable manner to make full use of their intrinsic properties in optical and electronic device applications. [4] This represents a considerable challenge, since most conventional techniques used for dielectric or metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…Therefore, the absence of reactive sites on 2D materials causes nonuniform and uncontrolled film quality with poor coverage and predominant nucleation at sites of defects or impurities (Figure a). In addition, it has been reported that the ALD process can induce changes in the electrical properties of 2D materials due to their surface-sensitive characteristics. , To address this issue, recent advancements have included the modification of surface properties of 2D materials or the introduction of seeding layers prior to ALD.…”
Section: D Film Deposition With Pretreatment For 3d-on-2d Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the absence of reactive sites on 2D materials causes nonuniform and uncontrolled film quality with poor coverage and predominant nucleation at sites of defects or impurities (Figure a). In addition, it has been reported that the ALD process can induce changes in the electrical properties of 2D materials due to their surface-sensitive characteristics. , To address this issue, recent advancements have included the modification of surface properties of 2D materials or the introduction of seeding layers prior to ALD.…”
Section: D Film Deposition With Pretreatment For 3d-on-2d Integrationmentioning
confidence: 99%
“…In addition, it has been reported that the ALD process can induce changes in the electrical properties of 2D materials due to their surfacesensitive characteristics. 9,10 To address this issue, recent advancements have included the modification of surface properties of 2D materials or the introduction of seeding layers prior to ALD.…”
Section: D Film Deposition With Pretreatment For 3d-on-2d Integrationmentioning
confidence: 99%